2017
DOI: 10.3390/met7060199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Experimental Parameters on the Extraction of Silica and Carbonation of Blast Furnace Slag at Atmospheric Pressure in Low-Concentration Acetic Acid

Abstract: Blast furnace slag (BFS), a calcium-rich industrial byproduct, has been utilized since 2005 as a mineral carbonation feedstock for CO 2 sequestration, producing calcium carbonate precipitates. In this study, the conditions for the dissolution of Ca and Si in acetic acid, and subsequent carbonation, were elaborated. For this purpose, the retardation of the polymerization of silicon was attempted by varying the concentration of acetic acid, temperature, and leaching time. An inductively coupled plasma (ICP) anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
(30 reference statements)
1
10
0
Order By: Relevance
“…Granulated BFS was obtained from a steel making company in Pohang, Korea [17]. The sample was crushed and powdered to obtain particles ranging from 75 to 300 µm in size.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Granulated BFS was obtained from a steel making company in Pohang, Korea [17]. The sample was crushed and powdered to obtain particles ranging from 75 to 300 µm in size.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study demonstrated that carbonation could be performed via two methods using the extracted solution: One was to carbonate after separating the silica-rich gel, while the other was to carbonate all the leachates [17]. In this study, during the former process, impurities containing dissolved divalent cations such as Ca and Mg were elaborated to remain as much as possible in solution for the preparation of pure Si-Al nanoparticles.…”
Section: Synthesis Of Silica-alumna Compositesmentioning
confidence: 99%
See 3 more Smart Citations